Develop student attendance module software interface with biometric reader / Mohammad Nizam Hamzah - Hamzah, Mohammad Nizam (2006)
Generally, this project will develop a recording system of student details and attendances information in a database. A biometric system is essentially a pattern recognition system that makes personal identification by determining the authenticity of a specific physiological of behavioural characteristic possessed by the user. The model will be designed using Visual Basic, Structured Query Language (SQL) and interfacing using biometric reader. This paper presents the development of student attendance module software interface with biometric reader that may overcome the limitations of the existing system being implements. The limitations that occurred in the existing system were that the attendance could be cheat by the students who will sign on behalf of friend which not attend to the class. Lecturers are also having difficulty on the recording of the attendance if they have multiple classes and various types of students. Hopefully by having this system we can reduces the absences of students to class and help lecturers on the recording of the attendance.